2017
DOI: 10.1002/jcb.25890
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Promotes Doxorubicin‐Induced Pgp and BCRP Expression in Colon Cancer Cells Under Hypoxic Conditions

Abstract: P-glycoprotein (Pgp) and breast cancer resistance protein (BCRP) are ATP binding cassette (ABC) transporters that are overexpressed in different drug-resistant cancer cell lines. In this study, we investigated whether doxorubicin promotes Pgp and/or BCRP expression to induce drug resistance in colon cancer cells under hypoxic conditions. We analyzed HIF-1α activity via ELISA, Pgp, and BCRP expression by qRT-PCR and the relationship between doxorubicin uptake and ABC transporter expression via confocal microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…For example, Lin and colleagues showed that inhibition of AXL reversed EMT in prostate cancer cells, but they did not assess whether chemosensitivity could be restored with AXL knockdown [25]. Similarly, several reports suggest that inhibition or knockdown of AXL reduces the resistance of mesenchymal cells to chemotherapeutic drugs while also reverting them to an epithelial state [18, 33, 38, 50, 51]. Our finding that inactivation of AXL improves chemosensitivity without affecting the mesenchymal phenotype indicates that AXL directly regulates chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lin and colleagues showed that inhibition of AXL reversed EMT in prostate cancer cells, but they did not assess whether chemosensitivity could be restored with AXL knockdown [25]. Similarly, several reports suggest that inhibition or knockdown of AXL reduces the resistance of mesenchymal cells to chemotherapeutic drugs while also reverting them to an epithelial state [18, 33, 38, 50, 51]. Our finding that inactivation of AXL improves chemosensitivity without affecting the mesenchymal phenotype indicates that AXL directly regulates chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Fold change was calculated using the 2(x0005E)(-ΔΔCT) method. Primer sequences were previously published [9, 38, 39]. …”
Section: Methodsmentioning
confidence: 99%
“…mRNA expression was normalized with respect to glyceraldehyde-3-phosphate dehydrogenase, and fold change was calculated by the 2 (ÀDDCT) method. Primer sequences were previously published (18,(24)(25)(26).…”
Section: Cdna Preparation and Quantitative Real-time Pcrmentioning
confidence: 99%
“…35 The modulation of glucose levels and the oxidative stress also induces HIF-1α and MDR1 expression. 36,37 MDR1 is also regulated at RNA level by micro RNAs (miR) such as miR-145, miR-27a and miR-331-5p that bind directly the 3ʹUTR of ABCB1 mRNA to decrease MDR1 expression. 38,39 Some other miR (miR-137) indirectly decrease MDR1 expression by targeting the YB-1 transcription factor that upregulates MDR1 expression by fixation on ABCB1 promoter.…”
Section: Introductionmentioning
confidence: 99%